2018
DOI: 10.1177/0009922818759319
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in the Pediatric Emergency Department: Are We Considering Abuse?

Abstract: Approximately one fourths of infant fractures are due to abuse. Recognition of abuse is important to avoid further morbidity/mortality. There is limited knowledge regarding how frequently pediatric emergency department clinicians consider abuse in infants with fractures. Our primary objective was to estimate the percentage of infants with fractures for whom abuse was considered, and to examine characteristics associated with abuse consideration. We performed a retrospective review of infants <1 year of age pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Nineteen (26%) studies focused specifically on injury patterns of abused children, and the likelihood of child abuse among patients presenting with fractures, head trauma, and oral injuries. 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen (26%) studies focused specifically on injury patterns of abused children, and the likelihood of child abuse among patients presenting with fractures, head trauma, and oral injuries. 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases.…”
Section: Resultsmentioning
confidence: 99%
“…Second, future research could consider the drivers of, interventions for, and consequences of racial and ethnic bias in addressing child maltreatment. Such research could expand on work previously done in this area …”
Section: Considering Alternative Approaches To Address Child Maltreat...mentioning
confidence: 88%
“…3,6,7,19 The diagnosis of violence in the health sector 1,2,6,7,19 and notification to the responsible bodies avoids worse outcomes, such as emotional and physical sequelae and even death, especially in cases in which the victim suffers several aggressions over time in a chronic form. 1,6,7,10,11,[19][20][21][22][23] Whereas neglect is the most frequent type of child abuse, 2,3,7,11,23,24 it is observed that the incidence of injuries…”
Section: Introductionmentioning
confidence: 99%
“…O diagnóstico da violência no setor saúde 1 2 6 7 19 e a notificação aos órgãos responsáveis evitam piores desfechos, como sequelas emocionais, físicas e até óbito, principalmente em casos nos quais a vítima sofre diversas agressões ao longo do tempo de forma crônica. 1 6 7 10 11 19 20 21 22 23 Considerando que a negligência é o tipo mais frequente de maus-tratos infantis, 2 3 7 11 23 24 observa-se que a incidência de lesões nesses casos pode ser reduzida por meio da abordagem preventiva junto aos pais, orientando evitar cenários propensos a acidentes, incluindo os típicos de cada idade. 2 6 7 19…”
Section: Introductionunclassified
See 1 more Smart Citation